A lesson plan for teaching beginning reading and its theoretical basis - Culaba, Dena S. (Tanglaw: official journal of the College of Education, 2003)
This article presents a literature-based lesson plan that teaches beginning readers strategies to construct meaning through transaction with the text. To facilitate this meaning construction, teachers read stories to young children which also provides the context for language and phonics instruction. How the teacher's selection of the story reflects her own beliefs and knowledge of the story theme as well as of her pupil's developmental level and characteristics are also discussed. Before the story is read, children's prior knowledge is activated. As children listen to the story, they are taught the skills of predicting and confirming. After listening to the story, children are provided engagement activities that facilitate critical thinking and discussion of the story using the GPU format. Lessons in language and phonics that are anchored on the story text follow.